Globalization of European top-tier higher education institutions: allying or acquiring/merging - Sperlich, Mischa David (2023)
Based on an integration of an amalgamation of previous studies on the ally versus merge or acquire issue and an overview of the context around and drivers for higher education globalization, an unambiguous tendency towards forming strategic alliances rather than engaging in mergers or acquisitions could be deduced. Mergers and acquisitions, nevertheless, shall also be genuinely considered in some instances. None of the ally versus acquire or merge choices – based on pertinent decision factors – are likely to evolve in the short to mid run. The human side turns out to be central to both strategic alliances and mergers and acquisitions